Occurrence of cyanobacteria and microcystins in hydroelectric reservoirs used for fish farming - Falcone-Dias, Maria Fernanda; Rodrigues, Marianna Vaz [UNESP]; Nielsen, Jeppe Lund; De Jonge, Nadieh; Jørgensen, Niels O. G.; Alonso, Diego Peres [UNESP]; David, Gianmarco S.; Da Silva, Reinaldo José [UNESP]; Araújo, João Pessoa [UNESP] (IWA Publishing, 2020)
Fish farming can have a negative impact on water quality and aquatic organisms due to emerging blooms of Cyanobacteria and the production of cyanotoxins. In this study, the effect of aquaculture in hydroelectric reservoirs in Brazil was evaluated in six fish farms and in upstream and downstream water through analysis of the microbiome, Cyanobacteria and microcystin concentrations. Synechococcus and Microcystis were observed at all six locations, while Limnothrix was also observed abundantly at two locations. An increase in the relative abundance of Cyanobacteria inside the fish farms was observed at two locations, while an increase of Cyanobacteria was observed in downstream at five of the six locations. Microcystins were detected in significant and high values in all locations, with concentrations up to 1.59 ìg/L. The trend in microcystin concentrations was mirrored in copy numbers of the mcyE gene (encodes microcystin synthetase) and presence of Microcystis, but not in any of the other observed cyanobacterial groups. In summary, the study shows that aquaculture production influenced the water microbiome inside and downstream the fish farms, and a direct correlation was found between mcyE gene copies, microcystin production and abundance of Microcystis, but not for the total abundance of Cyanobacteria.
Keywords: Amplicon sequencing; Aquaculture; Cyanobacteria; Microbiome; Microcystins; Water quality